Activation of autophagy in periodontal ligament mesenchymal stem cells promotes angiogenesis in periodontitis. Issue 6 (10th July 2018) - Wei, Wei; An, Yulin; An, Ying; Fei, Dongdong; Wang, Qintao
Abstract: Background: Angiogenesis alteration in tooth support tissue plays an essential role in periodontitis. Mesenchymal stem cells (MSCs) can affect vessel formation by endothelial cells (ECs) through paracrine function. Autophagy is reported to be closely related to cell secretion. Here we investigated the angiogenesis‐promoting ability of MSCs that reside in the periodontal ligament (known as periodontal ligament stem cells, PDLSCs) under inflammatory conditions in order to explore the mechanism of angiogenesis alteration in periodontitis. Methods: PDLSCs were isolated from healthy and inflamed human periodontal ligament tissues (HPDLSCs and PPDLSCs, respectively). HPDLSCs were subjected to an inflammatory environment (IPDLSCs) in vitro using inflammatory cytokines. Angiogenesis‐promoting cytokine expression and autophagy were evaluated in PDLSCs by quantitative reverse transcription‐polymerase chain reaction and western‐blot analysis before co‐culturing them with ECs. The angiogenesis ability of ECs in the co‐culture system was examined by a matrigel tube formation test. Rapamycin and pcDNA for Beclin‐1 (cDNA‐Beclin‐1) were used to promote autophagy in PDLSCs and siRNA Beclin‐1 (siBeclin‐1) was used to repress it. Results: The inflammatory environment increased autophagy and the expression of basic fibroblast growth factor (bFGF) and angiogenin (Ang) in PDLSCs. More tube formation was observed in ECs from the co‐culture system which was pretreated with tumor necrosis factor (TNF)‐α and interleukin (IL)‐1β. PDLSCs treated with rapamycin or transfected with cDNA‐Beclin‐1 showed higher expression levels of bFGF and Ang that promoted tube formation by the co‐cultured ECs. PDLSCs transfected with siBeclin‐1 resulted in the opposite results. Conclusion: Autophagy modulates angiogenesis‐promoting ability of PDLSCs, which could be increased by an inflammatory environment.